2023
DOI: 10.1108/apjml-12-2022-1018
|View full text |Cite
|
Sign up to set email alerts
|

Transforming customers into evangelists: influence of online brand experience on relationship quality and brand evangelism in the banking industry

Abstract: PurposeCustomer relationships and transforming customers into evangelists are imperative in today's world. Therefore, this study aimed to examine the influence of online brand experience (OBE) on brand evangelism (BEM) via relationship quality (trust-TRT, satisfaction-SAT, and commitment-CMT) by integrating the moderating effects of brand reputation (BR), particularly in the Vietnamese banking sector.Design/methodology/approachThis research obtained data from 486 Vietnamese customers who routinely used online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Second, this study advances the U&G theory by demonstrating that firm-created social media communication substantially influenced perceived values (functional, emotional, and social values) and brand evangelism in the luxury hotel sector, enhancing gratifications. Customers are motivated to act as brand evangelists for the company when they experience the highest level of gratification (Safeer and Le, 2023). Third, this study demonstrated that perceived values (functional and emotional) motivate customers to become brand evangelists.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study advances the U&G theory by demonstrating that firm-created social media communication substantially influenced perceived values (functional, emotional, and social values) and brand evangelism in the luxury hotel sector, enhancing gratifications. Customers are motivated to act as brand evangelists for the company when they experience the highest level of gratification (Safeer and Le, 2023). Third, this study demonstrated that perceived values (functional and emotional) motivate customers to become brand evangelists.…”
Section: Discussionmentioning
confidence: 99%
“…A well-managed and responsive supply chain reflects positively on a brand's reputation [20]. Brand experience helps transform satisfied customers into enthusiastic advocates or promoters of a firm's product, service, or brand (evangelists) [21]. Agile SC requires three main enablers: a collaborative network of partners, information systems and technologies, and knowledge management.…”
Section: Supply Chain Strategies: Lean and Agile Strategiesmentioning
confidence: 99%